The effectiveness of attached growth process by using waste material for the treatment of leachate/Noorul Faidzani Mohd Fauzi - Mohd Fauzi, Noorul Faidzani (Faculty of Civil Engineering, 2006)
Leachate from a sanitary landfill needs to be treated effectively before it can be discharged to the environment. This study is concentrate for Idaman Bersih Sdn. Bhd. landfill in Pulau Burung, Pulau Pinang. The leachate influent and effluent data will collected and analysed in order to find out the percentage removal of the leachate parameters and to determine waste material (cockles shell) can improve preliminary treatment of leachate. This cockles shell will filter the organics before goes to the primary treatment. The effectiveness of attached growth process by using waste material for treatment of leachate is evaluate by looking at the parameters of leachate such as BOD, COD, VSS, SS, temperature, pH and conductivity. The process is operating under semi anaerobic condition. The data will be analyses by plotting graph and comparison of leachate quality before and after treatment is made to evaluate the effectiveness of the leachate treatment used in Idaman Bersih Sdn. Bhd in the preliminary treatment in leachate treatment plant. It is expected that the percentage removal of VSS, SS and BOD is better for 35 days retention time. The shell of the cockles will be the waste and this is the way to reuse the waste in leachate treatment in order to safe cost. In the same time we are doing the recycling waste.